The Effectiveness of Using Blooket Gamification in Increasing Motivation and Understanding of Pancasila Education Learning Concepts at SMPN 3 Banawa - Febriana M. Pagisi; Jamaludin Jamaludin; Hasdin Hasdin (Green Publisher Indonesia, 2025)
This study aims to analyze the implementation and effectiveness of gamification-based learning media in improving motivation and understanding of Pancasila Education concepts at SMP Negeri 3 Banawa. The research method used a descriptive interpretive qualitative approach with 110 eighth-grade students as research subjects. Data collection techniques included concept comprehension tests, learning motivation questionnaires, participatory observation, and in-depth interviews. The results of the study showed a significant increase in concept comprehension with an average post-test score of 74-78, up from 37-45. Student learning motivation increased substantially in all aspects: intrinsic motivation (85-93%), extrinsic motivation (83-88%), active involvement (85-93%), perseverance and effort (84-87%), and attitude towards the subject (83-91%). Blooket game-based learning proved to be effective in changing students' perceptions of Pancasila Education into a fun, interactive, and meaningful learning experience.